Taboo. Season one [videorecording (DVD)] - Hardy, Tom, 1977-; Hardy, Tom, 1977-; Bill, Leo; Buckley, Jessie, 1989-; Chaplin, Oona, 1986- (Echo Bridge Home Entertainment, 2018)
Danger-courting excursionist James Delaney returns to London in 1814 in order to attend his father's funeral. He not only inherit his notorious father's shipping empire, but all the enemies and debts created by his father's dubious dealings.